Smart structures through nontraditional design of Tuned Mass Damper Inerter for higher control of base isolated systems. (April 2020) - Masnata, Chiara; Di Matteo, Alberto; Adam, Christoph; Pirrotta, Antonina
Highlights: A smart structure strategy is proposed resorting to a nontraditional design of Tuned Mass Damper Inerter (New-TMDI) for base isolated structures. Optimal design of the New TMDI is studied. A straightforward solution for the optimal design of the New TMDI parameters is derived. Analyses are performed considering random base excitations and real earthquake records. Abstract: This paper introduces a smart structure design through the definition of an innovative passive control strategy, referred to as New Tuned Mass Damper Inerter (New TMDI), coupled with a base isolation system (BI), to control displacements in base isolated structures under seismic excitations. The herein proposed New TMDI comprises a recently developed nontraditional Tuned Mass Damper (known as New TMD), in which a secondary mass system is connected to the base plate of the BI system by a spring and to the ground by a dashpot, and of an inerter device placed in parallel with the damper. An optimization procedure which minimizes the base displacement variance of the BI system, considering the case of white noise base excitation, is proposed to determine optimal design parameters of the New TMDI, and pertinent approximate closed-form expression are derived. Note that, this device might be considered for applications in historic buildings, generally built in contiguity with the others. Adopting this nontraditional TMDI, it would be possible to get a smart historic building, offering higher control performance over an ordinary design. Further, the performance of a base-isolated New TMDI-controlled multi-degree-of-freedom structure is examined and compared with that of the simple base-isolated one, using a set of 44 recorded ground motions as base excitation. Results show that the New TMDI is rather effective in reducing the response of base-isolated structures under strong earthquakes.